2022
DOI: 10.14740/wjon1464
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis Secondary to Immune Checkpoint Inhibitor Therapy

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a fatal systemic inflammatory syndrome. HLH has been reported as a rare immune-related adverse event (irAE) in patients receiving immunotherapy with nivolumab, ipilimumab, and/or pembrolizumab. The data are limited to case reports and case series. The objective of this research is to compile data on this rare but potentially life-threatening adverse event of immune checkpoint inhibitors (ICIs) and identify the common agents that cause this irAE, clinical spectrum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Medicationinduced HLH is a rare entity with few prior published case reports and even fewer associated with antibiotics. [8][9][10][11][12][13] The mechanism of the association between medications and HLH is unclear and there are no established guidelines for treatment of these patients. Patients with medication-induced HLH were not specifically included in the HLH-94 or HLH-2004 trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicationinduced HLH is a rare entity with few prior published case reports and even fewer associated with antibiotics. [8][9][10][11][12][13] The mechanism of the association between medications and HLH is unclear and there are no established guidelines for treatment of these patients. Patients with medication-induced HLH were not specifically included in the HLH-94 or HLH-2004 trials.…”
Section: Discussionmentioning
confidence: 99%
“…The causative agent for HLH in this patient was likely TMP/SMX given the time course from the offending agent, no use of other medications, no other significant medical history and no underlying malignancy or other systemic condition identified. Medication-induced HLH is a rare entity with few prior published case reports and even fewer associated with antibiotics 8–13. The mechanism of the association between medications and HLH is unclear and there are no established guidelines for treatment of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A worth mentioning extremely rare adverse effect is hemophagocytic lymphohistiocytosis (HLH) as it is life threating with a high mortality rate and considered to be a serious complication [65]. Therefore, a patient presenting with severe inflammatory syndrome with associated fever, cytopenias and splenomegaly should prompt a full clinical work-up, including analysis of bone marrow aspirates and/or biopsy samples for the presence of hemophagocytic signs [65].…”
Section: Hematological Immune-related Adverse Eventsmentioning
confidence: 99%
“…For instance, epidemiology was reviewed in pancreatic cancer by Rawala et al [ 1 ], in prostate cancer by Cassell et al [ 2 ] and Rawala [ 3 ], in renal cell carcinoma by Padala et al [ 4 ], and in malignant melanoma by Naik [ 5 ]. Review articles also provide an opportunity to learn about the latest updates and summaries on relatively rare conditions such as male breast cancer [ 6 ], urothelial carcinoma [ 7 ], mucoepidermoid carcinoma [ 8 ], retroperitoneal liposarcoma [ 9 ], and even on hemophagocytic lymphohistiocytosis, a relatively rare side effect of immune checkpoint inhibitor therapy [ 10 ]. There were several review articles on topics that apply to all types of cancer, such as infections in hospitalized cancer patients [ 11 ], genetic polymorphisms [ 12 ], tumor dormancy [ 13 ], and unstable psychiatric disorder [ 14 ].…”
mentioning
confidence: 99%
“…In addition, we have noticed that there has been a huge increase in cancer immunology and immunotherapy interest. On immune checkpoint inhibition alone, Minami et al reported that sarcopenia and visceral adiposity did not affect its efficacy in lung cancer [ 31 ], Aly et al reported its use in sarcomatoid renal cell carcinoma [ 32 ], Tarekegn et al reported its use in relapsed/refractory classical Hodgkin lymphoma [ 33 ], Li et al reported its surrogate endpoints for gastro-esophageal carcinoma [ 34 ], and Rajapakse et al summarized one of its side effects [ 10 ]. Given the global pandemic of COVID-19 starting from 2020, our journal published three articles on this topic.…”
mentioning
confidence: 99%